Acute gastrointestinal injury and altered gut microbiota are related to sepsis-induced cholestasis in patients with intra-abdominal infection: a retrospective and prospective observational study - Zhang, Beiyuan; Chen, Xiancheng; He, Chenhang; Su, Ting; Cao, Ke; Li, Xiaoyao; Duan, Jianfeng; Chen, Ming; Zhu, Zhanghua; Yu, Wenkui (Frontiers in Medicine, 2023)
Background: Sepsis-associated liver dysfunction (SALD) has high incidence and mortality in patients with intra-abdominal infection (IAI). The associations between acute gastrointestinal injury (AGI), gut microbiota, and SALD were evaluated in patients with IAI. Methods: A retrospective study was conducted to assess the relationship between AGI and SALD in patients with IAI. Patients were divided into non-SALD and sepsis-induced cholestasis (SIC) groups, which is a subtype of SALD. SIC was defined as total bilirubin > 2 mg/dL. AGI incidences between the two groups were compared using Chi-square test. Subsequently, a prospective study was conducted to investigate the gut microbiota differences between patients without SALD and those with SIC. Fecal samples were collected on days 1, 3, and 7 after admission to analyze changes in gut microbiota using 16S ribosomal ribonucleic acid sequencing. Results: 134 patients with IAI were included retrospectively, with 77 SALD and 57 non-SALD cases. Among patients with SALD, 71 were diagnosed with SIC. Patients with SIC had a higher incidence of AGI compared to those without SALD (28.07% vs 56.34%, p < 0.05), and a severity-dependent relationship was found between AGI grade and SIC occurrence. Subsequently, 20 patients with IAI were recruited prospectively, with 10 patients each assigned to the non-SALD and SIC groups. Patients with SIC had a more severe gut microbiota disorder on day 7 than those without SALD, including lower microbiota diversities, decreased abundance of Firmicutes and Bacteroidetes, and increased abundance of Proteobacteria and Actinobacteria at the phylum level. Furthermore, Burkholderia−Caballeronia−Paraburkholderia and Delftia, the two most abundant genera, were significantly higher in the SIC group than in the non-SALD group. Functional prediction analysis showed that the top three KEGG pathways were ribosome, pyrimidine metabolism, and the two-component system. During the first week, the abundance of Proteobacteria decreased significantly, whereas Cyanobacteria increased in the non-SALD group; however, the phyla taxa did not change significantly in the SIC group. Conclusions: There exists a severity-dependent relationship between AGI grade and SIC occurrence in adult patients with IAI. A severe gut microbiota disorder was discovered in SIC during the first week of the intensive care unit stay.